Pathophysiology of Myopenia in rheumatoid arthritis - Haiming Jin; Gang Wang; Qichen Lu; Jessica Rawlins; Junchun Chen; Saanya Kashyap; Oscar Charlesworth; Dan Xu; Lie Dai; Sipin Zhu; Jiake Xu (Bone Research)
Abstract Rheumatoid arthritis (RA) is a prevalent and debilitating inflammatory disease that significantly impairs functional capacity and quality of life. RA accelerates musculoskeletal aging, leading to complications such as muscle degeneration and sarcopenia. Recent research has identified myopenia as a condition of significant muscle loss associated with illness, distinct from the muscle wasting seen in other chronic diseases like cancer cachexia or heart failure. In RA, myopenia is characterized by muscle depletion without concurrent significant fat loss, and it can affect individuals of all ages. While inflammation plays a central role, it is not the sole factor contributing to the high incidence of muscle wasting in RA. In subsequent discussions, secondary sarcopenia will be considered alongside myopenia, as both involve muscle wasting decline primarily due to disease. This review summarizes recent findings on the impact of RA-related myopenia and secondary sarcopenia on functional capacity, explores its underlying mechanisms, and discusses contemporary strategies to mitigate the process of musculoskeletal aging in RA patients.